Clinical and Laboratory Study of Patients with Operated Hydatid Cysts - Azadeh Dadashi; Farhang Babamahmoodi; Mahdi Fakhar; Hajare Ziaei Hezarjaribi; Niloofar Amin; Bahman Rahimi; Shirzad Gholami (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Studying the different diagnostic aspects of hydatid cysts (HC) plays a major role in early diagnosis and treatment. This study was conducted to evaluate the clinical and laboratory characteristics of HC cases operated in educational hospitals affiliated with Mazandaran University of Medical Sciences. Materials and methods: In this descriptive study, the records of all cases with HC (n=95) who underwent surgical treatment in two educational hospitals within 11 years (2004-2015) were studied and analyzed. Results: The patients were found to be 53.7% females, 67.4% living in rural areas, and 28.4%  were aged 51-60 years old (P<0.05). Liver, lung, and spleen had the highest involvement of HC, respectively. Imaging techniques were used to diagnose the HC along with clinical symptoms. Conclusion: The present study showed that HC still remains a health problem in Mazandaran province, especially in rural areas.